A Comprehensive Approach for E-Government Solutions - Cortés-Morales, Roberto (2017)
Experiences on developing E-government solutions have given a set of evidences that policy makers can profit in order to avoid poor results or to adopt best practices. Complexities on such solutions involve several considerations that should be managed using multiple variables related to different dimensions including political, economic, social, administrative and technological ones. Integrating theoretical principles from Public Value, Public Policies and Multidimensional Actor Model, could derive on a particular approach for the design of policies where E-government supports a political goal. Some cases are referred for illustrate this approach.